TRADISI KALANGKAH DALAM PERKAWINAN ADAT SUNDA PERSPEKTIF ‘URF (Studi Kasus di Desa Pananjung Kec. Pangandaran Kab. Pangandaran) - Yasir Fauji (JURNAL ILMIAH NUSANTARA, 2025)
Yasir Fauji. 1991014087. 2023. Kalangkah Tradition in Sundanese Traditional Marriage from ‘Urf persepective (Case Study in Pananjung Village, Pangandaran District, Pangandaran District). This research is motivated by the existence of traditions in Sundanese traditional marriages which are still ongoing and believed by the community, precisely in Pananjung Village, Pangandaran District, Pangandaran Regency, namely about traditions.what a stepTradition what a stepor Surrenderknown as the prohibition for a younger sibling to marry before their older sibling. Some people believe that there will be bad impacts that will befall those who step over or those who are stepped over if they violate this tradition. However, there are also quite a few people who do not believe in the impact of breaking this tradition, because it is only considered a mere suggestion or myth, which was passed down from previous ancestors. This research is a type of qualitative field research. By using a sociological approach. The method used in data collection techniques is through observation, interviews and documentation. The results of this research concluded that the kaangkat tradition prohibits a younger brother or sister from marrying before their older sibling. Some people in Pananjung Village believe that the consequences of breaking this tradition include disharmonious households, older siblings who are stepped on, having difficulty finding a mate and so on. According to the opinion of community leaders in Pananjung Village, the impact of breaking this tradition is only a suggestion, because everything has become Qada and Qadar of Allah SWT. In the application of Islamic law, the prohibition on customary marriage is not a problem as long as it does not conflict with religious and state regulations. As contained in the 'Urf theory, customs can become law in the customary area. So that people can continue to preserve traditionswhat a stepwithout contradicting Islamic law.